Peningkatan pengetahuan masyarakat terhadap manfaat Bunga Rosella (Hibiscus sabdariffa l.) dalam pencegahan infeksi bakteri Enterobacter aerogenes - Siti Rohani; Trisnawati Trisnawati; Sinta Julia; Agnes Melianti (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Biodiversity is one of Indonesia's riches. One of Indonesia's biodiversity is the Rosella plant (Hibiscus sabdariffa L). Rosella is believed to have benefits because the content of substances contained in it provides a synergistic effect so that it can prevent several health problems. Muara Dua and Pulau Panggung Village in Muara Enim, South Sumatra, is known as one of the areas in Indonesia that produces Rosella flowers widely. The community has a habit of consuming Rosella and this plant has many health benefits because it contains substances in the form of flavonoids, saponins, tannins and alkaloids which have antibacterial activity. The aim of this community service activity is to increase public understanding of the benefits of Rosella plants in preventing infections caused by the bacterium Enterobacter aerogenes. The community service activity involves socialization and education in the form of an offline counseling session. Pre-tests and post-tests were conducted before and after the counseling to assess whether the counseling had any impact. The results, based on 48 respondents with 10 questions, were evaluated using statistical tests from the pre-test and post-test data. The Wilcoxon Signed Rank Test approach was applied, and the negative ranks value indicated a difference in outcomes after the counseling. The asymptotic significance (2-tailed) value was 0.000, and the Z-score value of -5.845 indicates a significant improvement in the respondents' knowledge after the counseling session. The conclusion of this community service activity demonstrates a significant increase in public understanding regarding the benefits of Roselle flowers as a medicinal preparation for combating Enterobacter aerogenes bacterial infections.